(untitled) (Global Journal of Science Frontier Research, 2024)
The article discusses the physical reasons for the discrepancies between the observed and calculated values of the perihelion displacement of the planet Mercury Based on numerous data obtained by domestic and foreign authors the reasons for such differences are indicated The possibility of introducing into calculations of the dynamics of planets in the terrestrial system practical values of the gravitational constant related to the specific terrestrial systems under consideration is substantiated The article is accompanied by valuable analytical and numerical estimates